2015
DOI: 10.5688/ajpe79688
|View full text |Cite
|
Sign up to set email alerts
|

Career Placement of Doctor of Pharmacy Graduates at Eight U.S. Midwestern Schools

Abstract: Objective. To characterize postgraduation placement plans of 2013 doctor of pharmacy (PharmD) graduates. Methods. A cross-sectional survey of PharmD graduates from 8 midwestern colleges of pharmacy was designed to capture a comprehensive picture of graduating students' experiences and outcomes of their job search. Results. At graduation, 81% of 2013 respondents had postgraduate plans, with approximately 40% accepting jobs and 40% accepting residencies or fellowships. Eighty-four percent of graduates reported b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 12 publications
0
9
1
Order By: Relevance
“…In this study, it took about 10 months to get an internship placement after graduation due to the increased number of pharmacists graduates annually and non increasing internship job placements. This finding is in stark contrast with that of the United States [12].…”
Section: Discussioncontrasting
confidence: 89%
“…In this study, it took about 10 months to get an internship placement after graduation due to the increased number of pharmacists graduates annually and non increasing internship job placements. This finding is in stark contrast with that of the United States [12].…”
Section: Discussioncontrasting
confidence: 89%
“…5 Considering that most student pharmacists will enter community pharmacy after graduation, student pharmacist experiential education in their core community pharmacy should include the provision of clinical services that align with current best practices to produce practice-ready pharmacists. 6,7 Various studies describe the impact that APPE-year student pharmacists have at their core community APPE practice sites. Many are related to MTM, which may include over-thecounter (OTC) medication counseling and also include specific disease states such as heart failure and diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these programs leading to non-traditional opportunities and career paths within the field of pharmacy, a study conducted by Sweet and others found only 4% of respondents applied for a fellowship, and what's more, only half of those were accepted into a fellowship program. Furthermore, a number of respondents pursuing post-doctoral training expressed desire for more information on pharmacy fellowships throughout the course of their Pharm.D education [1]. To address students' interest, this study aims to explore pharmacy fellowships as a path of post-doctoral training available to Pharm.D.…”
Section: Introductionmentioning
confidence: 99%
“…Saturation of the job market in the field of pharmacy has led more and more students to seek out post-doctoral training including residencies and pharmacy fellowships in hopes of maintaining a competitive edge [1]. ASHP defines pharmacy fellowship as "a directed, highly individualized, postgraduate program designed to prepare the participant to become an independent researcher" with the ultimate goal of preparing the fellow for both independent and collaborative scientific research [2].…”
Section: Introductionmentioning
confidence: 99%